SHERLOC Raman Mineral Class Detections of the Mars 2020 Crater Floor Campaign. Issue 3 (5th March 2023) - Corpolongo, Andrea; Jakubek, Ryan S.; Burton, Aaron S.; Brown, Adrian J.; Yanchilina, Anastasia; Czaja, Andrew D.; Steele, Andrew; Wogsland, Brittan V.; Lee, Carina; Flannery, David; Baker, Desirée; Cloutis, Edward A.; et al.
Abstract: The goals of NASA's Mars 2020 mission include searching for evidence of ancient life on Mars, studying the geology of Jezero crater, understanding Mars' current and past climate, and preparing for human exploration of Mars. During the mission's first science campaign, the Perseverance rover's SHERLOC deep UV Raman and fluorescence instrument collected microscale, two‐dimensional Raman and fluorescence images on 10 natural (unabraded) and abraded targets on two different Jezero crater floor units: Séítah and Máaz. We report SHERLOC Raman measurements collected during the Crater Floor Campaign and discuss their implications regarding the origin and history of Séítah and Máaz. The data support the conclusion that Séítah and Máaz are mineralogically distinct igneous units with complex aqueous alteration histories and suggest that the Jezero crater floor once hosted an environment capable of supporting microbial life and preserving evidence of that life, if it existed. Plain Language Summary: The goals of NASA's Mars 2020 mission include searching for evidence of ancient life on Mars, studying the geology of Jezero crater, understanding Mars' current and past climate, and preparing for human exploration of Mars. During the mission's first science campaign, SHERLOC (Scanning Habitable Environments with Raman and Luminescence for Organics and Chemicals), one of Perseverance rover's spectroscopic instruments, collected microscale, two‐dimensional images that displayed mineral and organic molecule detections on 10 natural (unabraded) and abraded targets on two different Jezero crater floor geological units: Séítah and Máaz. We report SHERLOC mineral detections made during the Crater Floor Campaign and discuss their implications regarding the origin and history of Séítah and Máaz. The mineral detections support the conclusion that Séítah and Máaz are igneous units with different mineral compositions and distinct histories of alteration by fluids. The detections further suggest that the Jezero crater floor was once home to an environment capable of supporting microbial life and preserving evidence of that life, if it ever existed. Key Points: The floor of the Jezero crater hosts distinct igneous units with differing aqueous alteration histories SHERLOC Raman mineral class detections indicate that the Jezero crater floor was once a habitable environment Some Crater Floor Campaign samples may contain salts known to preserve biosignatures in terrestrial analog environments